2017
DOI: 10.1177/2309499017716257
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life with long-term retention of the PROSthesis of Antibiotic Loaded Acrylic Cement system following infection resolution in low demand patients

Abstract: Further evaluation is required to determine whether longer term PROSTALAC retention may be appropriate for specific patient groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 17 publications
0
11
0
2
Order By: Relevance
“…Analyzing some studies, published in the past 5 years and extrapolating the epidemiological data reported in Table 1 , 11 12 13 14 15 16 17 18 we noticed how the incidence of Staphylococcus infection is the most frequent attending for almost 70% of the cases. Similar results are reported by Tande and Patel that reviewed 14 studies with a total of 2,400 patients.…”
Section: Microbiology: Which Bacteria Affect the Tha?mentioning
confidence: 84%
See 1 more Smart Citation
“…Analyzing some studies, published in the past 5 years and extrapolating the epidemiological data reported in Table 1 , 11 12 13 14 15 16 17 18 we noticed how the incidence of Staphylococcus infection is the most frequent attending for almost 70% of the cases. Similar results are reported by Tande and Patel that reviewed 14 studies with a total of 2,400 patients.…”
Section: Microbiology: Which Bacteria Affect the Tha?mentioning
confidence: 84%
“…We reviewed 14 articles found in literature 12 13 14 15 16 17 18 47 48 49 50 51 52 53 published in the past 10 years for a total of 7,912 patients. Data are collected and reported in Table 2 .…”
Section: Spacersmentioning
confidence: 99%
“…konnten in ihrer Fallserie mit individuellen Megaspacern nur bei 7 von 11 (64 %) Patienten eine Gelenkrekonstruktion vornehmen [ 12 ]. In einigen Kollektiven wurde der Hüftspacer in bis zu 36–68 % der Fälle als endgültiges Implantat belassen [ 12 , 29 ]. Für Spacer als Dauerimplantate werden hohe Versagensraten von bis zu 73 % beschrieben [ 30 ].…”
Section: Diskussionunclassified
“…Bei liegendem/persistierendem Spacer erzielen Patienten oft nur eine unbefriedigende Hüftfunktion gemessen am HHS von 37–60 Punkten [ 6 , 25 ]. Für Patienten mit erheblichen Komorbiditäten und reduziertem Mobilitätsanspruch ist dies jedoch meist akzeptabel, solange keine Spacerkomplikation auftritt [ 29 ]. Auch nach endoprothetischer Hüftgelenkrekonstruktion sind die funktionellen Ergebnisse selbst bei kleinen femoralen Defekten variabel und reichen im Durchschnitt von unbefriedigend bis bestenfalls gut (HHS: 64–89 Punkte) [ 6 , 8 ].…”
Section: Diskussionunclassified
“…[ 76 ] The ALBC spacer was found to be an optional successor for an infected prosthesis. Beaupre et al [ 77 ] measured the health-related quality of life (HRQL) of patients who received a revision THA. It was found that improvements in the HRQL appeared 3 to 6 months after spacer implantation.…”
Section: Clinical Applications Of Albcmentioning
confidence: 99%